LEGAL THINKING IN THEORY AND PHILOSOPHY OF LAW - Borodin, Ivan L.; Myronets, Oksana M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the necessity to use different approaches in a process of studying law as a complicated phenomenon has been substantiated in the article. Multidimensional legal thinking is important because a meaningful idea about the nature of law depends on approaches that have been used in its investigation. Methods: phenomenological; hermeneutic; comparative-legal; sociological; logical; dialectical. Results: the nature and the place of the category of “legal thinking” within the limits of such legal sciences as state and law theory and philosophy of law have been analyzed; the relationship between some types of legal thinking has been analyzed; the necessity, importance, expediency and relevance of the integrative jurisprudence formation for a modern society’s functioning has been substantiated. Discussion: legal thinking issues, law as a phenomenon, as an instrument for satisfying subjects’ of legal relations needs, the interrelation of certain types of legal thinking with the requirements of legality.